2023
DOI: 10.1210/clinem/dgad246
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23, Glucose Homeostasis, and Incident Diabetes: Findings of 2 Cohort Studies

Abstract: Background The phosphate-regulating hormone fibroblast growth factor 23 (FGF23) has been linked to deregulations in glucose metabolism, but its role is insufficiently understood. This study investigates potential cross-talk between FGF23 and glucose homeostasis. Materials and Methods First, we investigated the effect of glucose loading on plasma C-terminal FGF23 levels and its temporal relationship with changes in plasma phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Furthermore, FGF23 is positively associated with markers of insulin resistance and adiposity [ 12-14 ]. Recently we found that a higher plasma FGF23 is associated with incident diabetes in the general population [ 15 ]. To our knowledge, the present study is the first to investigate the association between FGF23 and PTDM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FGF23 is positively associated with markers of insulin resistance and adiposity [ 12-14 ]. Recently we found that a higher plasma FGF23 is associated with incident diabetes in the general population [ 15 ]. To our knowledge, the present study is the first to investigate the association between FGF23 and PTDM.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, FGF23 has been recognized as an important biomarker at the cardiovascular level [16,17]. In addition, it appears to be involved in iron metabolism [18], immune response [19], or glucose metabolism [20]. In this article, we will explore some of the recently discovered non-classical effects of FGF23.…”
Section: Introductionmentioning
confidence: 99%